A food and nutritional surveillance system for Ireland - Kelly, A.; Kevany, J. (Statistical and Social Inquiry Society of Ireland, 1981)
The need for a national food and nutrition policy is increasingly recognised by governments of developed as well as developing societies. Such policies represent an agreed strategy for the most efficient use of national food resources to meet health, social and economic priorities. Given the inter-relationships between food production, food supply, consumption and health effects, any strategy of this kind must involve several sectors, both public and private. The outcome of such a strategy would be a series of recommendations to be applied through sectoral programmes in order to achieve a comprehensive and co-ordinated approach to a set of common goals. Tentative policies have been established by some European governments while discussion of scope and content of policy has been undertaken by others. In Ireland, various public services and institutions have considered the need for such a policy and the health sector has defined a set of recommendations for policy consideration. To date, no multisectoral policy body has been established. However, in the second quarter of 1981, a university-based seminar was conducted to examine the needs and mechanisms for policy making in this area (coordinated by Matthews, 1981).
Read before the Society, 29 April 1981
Keywords: Food policy, Ireland; Nutritional surveillance, Ireland; Health policy, Ireland; 314.15